2004
DOI: 10.1016/j.jasms.2003.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Adduct formation in quantitative bioanalysis: Effect of ionization conditions on paclitaxel

Abstract: Quantitative analysis of target compounds with liquid chromatography atmospheric pressure ionization mass spectrometry is sometimes hampered by adduct formation. In these situations, cationization with alkali metal ions instead of proton addition is often observed in the positive ion mode. This work studies the process of adduct formation and investigates potential strategies to control this phenomenon. Paclitaxel, a pharmaceutical chemotherapeutic agent, was used as a model compound. Electrospray (ESI), atmos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
70
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 15 publications
5
70
0
Order By: Relevance
“…Ammonium adducts present several advantages including usually easier fragmentation [15] and the possibility of using both API interfaces [16 -18]. Different primary amines also have been tested for this purpose [16].…”
mentioning
confidence: 99%
“…Ammonium adducts present several advantages including usually easier fragmentation [15] and the possibility of using both API interfaces [16 -18]. Different primary amines also have been tested for this purpose [16].…”
mentioning
confidence: 99%
“…6 Furthermore, Zhao et al, 7 Mortier et al, 2 and Karnes' group 8,9 reported the same usefulness of alkylamines for simvastatin, paclitaxel, and docetaxel, respectively. Teshima et al investigated an application of 1-alkylamines for quantitative analysis using LC/ESI-MS, [10][11][12] while other chemicals have been studied as well.…”
Section: Introductionmentioning
confidence: 92%
“…Generally, ESI-MS results in protonated molecules, [M+H] + , in the positive-ion mode; however, for some molecules the formation of alkali metal ion adducts, like [M+Na] + or [M+K] + , instead of proton addition are often observed. When the process is not controlled, facile adduct formation can lead to large variations and unreliable results during the quantitative method development of drugs with LC/ESI-MS. 1,2 Modulating the temperature or voltage for the ESI condition is insufficient to completely suppress the formation of alkali metal ion adducts. 3 Neubauer and Anderegg reported that the addition of sodium acetate to the HPLC mobile phase during an LC/ESI-MS experiment encourages the formation of sodium adduct ions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefit of addition of ammonium ion in mobile phases for signal enhancement and reproducible analysis was demonstrated by several groups using small chemicals (37,38). We wanted to identify PtdInsPs from biological samples such as cells and mice livers, and also to obtain the relative quantitation of PtdInsPs.…”
Section: Ammonium Adducts For Ptdinspsmentioning
confidence: 99%